HUBUNGAN PARAMETER KUAT GESER LANGSUNG DENGAN INDEKS PLASTISITAS TANAH DESA NEUHEUN ACEH BESAR - Marwan Marwan; Reza Pahlevi Munirwan; Devi Sundary (JURNAL TEKNIK SIPIL, 2013)
This research aims to evaluate effect of soil plasticity index (PI) to shear strength parameters, e.i. the angle of shearing (φ) and cohesion value (c). Parameters of φ and c obtained from Direct Shear Test in soil mechanics laboratory. The soil samples used for the research were taken from Neuheun Village, Mesjid Raya Subdistrict, and Aceh Besar District. Based on AASHTO soil classification, the soil sample is a Group A-7-6, whereas based on USCS soil classification, the soil is sandy clay of CL symbol. Soil specimen for Undisturbed Sample (UDS) and Disturbed Sample (DS) were 20 samples respectively, each sample was made to be three sub samples. The result of research shows that there is a linier correlation of shearing angle to PI, i.e., φ = -0,700 IP + 47,474, R2 = 0.882 for Undisturbed Samples (UDS) and φ = -1,757 IP + 59,313, R2 = 0.891 for Disturbed Samples (DS). The result of research also shows there is a linier correlation of cohesion value to PI, i.e., c = -0,053 IP + 1,569, R2 = 0.887 for UDS and c = -0,076 IP + 1,882, R2 = 0.783 for DS. It can be concluded that shear strength parameters for all tested samples in this research influenced by soil plasticity index. The higher soil plasticity index resulted the lower Shear Strength Parameters.